The Influence of Work Ethic on Employee Job Satisfaction in Escort Bags Bandung Smes - Dinihayati, Erti; Putri, Amara Amelia (Universitas Pasundan, 2024)
UKM Escort luggage Bandung is a business that sells diverse fashions of college baggage, backpacks, pc luggage, shoulder luggage, sling luggage and the like. This study targets to decide and analyze the effect of labor ethic on employee job delight at UKM Escort baggage Bandung. The research technique used is a quantitative data type technique with an associative approach in the shape of a causal relationship (motive and effect). records collection on this take a look at used 2 (two) techniques, particularly number one facts and secondary information. number one data with non-player observation techniques, structured interviews, and questionnaires dispensed to 26 respondents the use of saturated sampling techniques. As for the secondary records with library research strategies, journals or articles, and the net. The technique used to analyze the information consisted of variable score analysis, validity check, reliability check, easy linear regression, pearson correlation, coefficient of dedication, and speculation checking out. based on the consequences of information processing via records evaluation techniques, a end result may be obtained that there is a considerable impact on paintings ethic on task pleasure.